eCM 2017
DOI: 10.22203/ecm.v033a20
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and limitations of Integra® flowable wound matrix seeded with adipose tissue-derived microvascular fragments

Abstract: Adipose tissue-derived microvascular fragments (ad-MVF) represent promising vascularisation units for bioengineered Integra ® matrix wound dressing (MWD). However, due to the sheet-like structure with small pore sizes, the seeding of this matrix with ad-MVF is mainly limited to its surface. Integra ® flowable wound matrix (FWM) may be suitable to achieve a more homogeneous distribution and, thus, improved vascularisation, because this gel-like matrix allows for the direct admixture of ad-MVF during sample prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
(28 reference statements)
1
21
0
Order By: Relevance
“…Using intravital fluorescence microscopy, we found that HD and MD ad-MVF-seeded Integra ® exhibited a comparable vascularisation over time, whereas LD ad-MVF-seeded implants were characterised by a significantly lower number of perfused ROIs and functional microvessel density. In line with these findings, additional photoacoustic measurements (Später et al, 2017). This process not only involves the interconnection of individual ad-MVF with each other but also the development of anastomoses with the surrounding vessels of the host tissue.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Using intravital fluorescence microscopy, we found that HD and MD ad-MVF-seeded Integra ® exhibited a comparable vascularisation over time, whereas LD ad-MVF-seeded implants were characterised by a significantly lower number of perfused ROIs and functional microvessel density. In line with these findings, additional photoacoustic measurements (Später et al, 2017). This process not only involves the interconnection of individual ad-MVF with each other but also the development of anastomoses with the surrounding vessels of the host tissue.…”
Section: Discussionsupporting
confidence: 74%
“…The vascularisation of the implants was assessed in 12 regions of interest (ROIs). ROIs exhibiting red blood cell (RBC)-perfused microvessels were defined and counted as perfused ROIs (in % of all ROIs) (Später et al, 2017). The functional microvessel density was determined as the total length of all RBC-perfused microvessels per ROI (cm/cm 2 ).…”
Section: Intravital Fluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, >95% of the microvessels within the prevascularized implants were GFP + , indicating that they originated from the seeded ad-MVF. This finding is important, because in contrast to previous studies 11 , 30 , 31 we herein used the double-layer Integra, which is covered with a silicone sheet. Hence, ad-MVF could only be seeded on the bottom side of the matrices and were implanted in direct contact to the bone of the mouse skull.…”
Section: Discussionmentioning
confidence: 99%
“…Under experimental conditions, ad-MVF have already been shown to improve the vascularization of random-pattern flaps, 31 superficial myocardium, 32 epicardial patches, 33 volumetric muscle defects, 34 pancreatic encapsulating devices, 35 and scaffolds for tissue engineering. 36 A major prerequisite to pave the way for the transfer of such applications into clinical practice is to evaluate whether the vascularization capacity of ad-MVF is affected by clinical routine procedures. In this context, we could herein demonstrate that enox does not impair the reassembly of ad-MVF into new microvascular networks within implanted dermal skin substitutes.…”
Section: Discussionmentioning
confidence: 99%